Alfabetização na escola primária em Diamantino - Mato Grosso (1930 a 1970) - Amâncio, Lázara Nanci de Barros (2006)
The study objected contribute for an alphabetization’s history formstion in Diamantino-MT, by the way of localization of the fonts that allowed the comprehension and analisys of the relations between the patterns (national and statual), subjects (theoretical produtions for the alphabetization) and the concretization (class diaries, statement of the inspector, register and declaration of the time subjects) searching rescues of a apropriation by the part of the teachers, subjects of the research, theses possibles orientations for your alphabetization practice. The historic mark remains in the turn of the decade of 1930 to 1970, comprehended between at the current of the Rule of the Public Instruction of Mato Grosso, from 1927, from that Laws of the Directrises and Basis – LDB 4.024/61 and 5.692/71.The investigation staffed in the pressupost of the cultural history, in a qualitative approach, by means of a research of historical profound, recoursing to a stand up, reunion, selection and a sistematization of the documental fountains and the pressupost of the spoken history.The dates analysis was realizated by the way of conduct of the analyses of the text configuration, in the basis on the conjoint of the normatizations, documental fountains, and the declaration of the involved subjects, searching the description, interpretation and comprehension, of that comparison and crossing of the dates. In the finish of the investigation, was possible to be known that the rule of 1927 prescribe, for the alphabetization instruction, the analitic method; the LDB 4.024/61, advise the instruction of the “national language”, without show a method and the 5.692/71 directs for the instruction of the “Comunication and the Expression”, advising “ value the reading, writing and the interpretation”.About the concretizations, evidenced like methodological recourse of note in the practice of the alphabetizator’s teachers, in the period in study, the books of alphabetization for the teaching of the reading, being that the teachers favored the books lesson and their activities.The way to teach (method) show with some variations and changes elapsed in the study period, with prevail the method of synthetical orientation, probability in function of the choice liberty and the singular way that each teacher teachs, whats reveal few indiciums or traces of a appropriate normatization for the practice of the diamantinenses teachers.